The pre-clinical absorption, distribution, metabolism and excretion properties of IPI-926, an orally bioavailable antagonist of the hedgehog signal transduction pathway. (25th March 2013) - Smith, Sherri; Hoyt, Jennifer; Whitebread, Nigel; Manna, Joseph; Peluso, Marisa; Faia, Kerrie; Campbell, Veronica; Tremblay, Martin; Nair, Somarajan; Grogan, Michael; Castro, Alfredo; Campbell, Matthew; et al.
Abstract: 1. IPI-926 is a novel semisynthetic cyclopamine derivative that is a potent and selective Smoothened inhibitor that blocks the hedgehog signal transduction pathway. 2. The in vivo clearance of IPI-926 is low in mouse and dog and moderate in monkey. The volume of distribution is high across species. Oral bioavailability ranges from moderate in monkey to high in mouse and dog. Predicted human clearance using simple allometry is low (24 L h −1 ), predicted volume of distribution is high (469 L) and predicted half-life is long (20 h). 3. IPI-926 is highly bound to plasma proteins and has minimal interaction with human α-1-acid glycoprotein. 4. In vitro metabolic stability ranges from stable to moderately stable. Twelve oxidative metabolites were detected in mouse, rat, dog, monkey and human liver microsome incubations and none were unique to human. 5. IPI-926 is not a potent reversible inhibitor of CYP1A2, 2C8, 2C9 or 3A4 (testosterone). IPI-926 is a moderate inhibitor of CYP2C19, 2D6 and 3A4 (midazolam) with KI values of 19, 16 and 4.5 µM, respectively. IPI-926 is both a substrate and inhibitor (IC50 = 1.9 µM) of P-glycoprotein. 6. In summary, IPI-926 has desirable pre-clinical absorption, distribution, metabolism and excretion properties.